The Perception of Gender in French Language for StudentsA study of Writing Productions in the Secondary School / Morocco (مجلة إحالات, 2026)
This article is part of a reflexion on the teaching and learning French particularly in its component of writing at secondary school in Morocco. This language, whose status varies, ineducational terms, between the language taught and the language of instruction, does pose problems and challenges in the teaching process. Our target audience in this study is common core students. The corpus is based on writing productions which we have studies and analysed so tohighlight the mistakes, in terms of gender, that are frequently made by students; these mistakes are attributed to the interference of their native language or language of communication while learning a foreign language.